Android malware family classification method based on the image of bytecodeConstruction of MDS matrices - Yi-min YANG; Tie-ming CHEN (网络与信息安全学报)
An Android malware family classification method based on the image of bytecode was proposed accord-ing to the exponential growth of Android malware.A bytecode file of Android malware was converted to a 256-level grayscale image and texture features was extracted from the image by GIST.The random forest algorithm was ap-plied to classify the extracted features.The method by the experimental data of 14 kinds of common Android mal-ware families was verified and was compared against the DREBIN on the same dataset.The experimental results show that the proposed method has high detection precision and low false positive rate.